An analysis of Singapore’s aware case - James, Kieran; Grant, Bligh; Kwai, Jenny Sim Leung (Penerbit UKM, 2013)
Our case involves the women’s group Association of Women for Action and Research (AWARE), founded on 25 November 1985, which has proven itself to be a tireless long-term campaigner for women’s rights in Singapore. In this ‘AWARE case’, the executive committee of AWARE was surreptitiously taken over by fundamentalist Christian women from Church of Our Saviour at AWARE’s 28 March 2009 Annual General Meeting. In the second phase of this saga, the Extraordinary General Meeting on 2 May 2009 led to the secular ‘Old Guard’ recapturing AWARE and the Church of Our Saviour group being removed from power. This AWARE case shows the rise in power of fundamentalist Protestant Christianity within Singapore and its growing influence upon English-educated Chinese-Singaporeans. The fact that this upper middle-class demographic traditionally has supported the ruling People’s Action Party (PAP) is probably one key reason why the government decided not to intervene in this particular case as part of ‘the more consultative style of government’ first introduced by former PM Goh Chok Tong. The PAP government’s non-intervention in the takeover and recapture is extremely significant given its past record of authoritarian micro-management of dissent and oppositional opinions. It suggests more freedom for some NGOs in the contemporary era of Lee Hsien Loong’s prime-ministership. Significantly, PAP may be splitting into ‘reformist’ and ‘hardline’ factions headed by, respectively, Lee Hsien Loong and the MP for Bishan-Toa Payoh GRC Mr Wong Kan Seng.